2023
DOI: 10.3390/diagnostics13010161
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Based Methods for Breast Cancer Diagnosis: A Systematic Review and Future Direction

Abstract: Breast cancer is one of the precarious conditions that affect women, and a substantive cure has not yet been discovered for it. With the advent of Artificial intelligence (AI), recently, deep learning techniques have been used effectively in breast cancer detection, facilitating early diagnosis and therefore increasing the chances of patients’ survival. Compared to classical machine learning techniques, deep learning requires less human intervention for similar feature extraction. This study presents a systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(37 citation statements)
references
References 126 publications
1
35
0
1
Order By: Relevance
“…As a subset of DL and the most common type of neural network, the CNN is suited to identify particular patterns in images which can occur at different locations because the convolution operation is spatially invariant (Burt et al 2018, Robertson et al 2018. In a systemic review, Nasser and Yusof found that CNN model has the most accurate performance with the most extensive application for breast cancer diagnosis (Nasser and Yusof 2023). A CNN consists of three layers: an input layer, a hidden layer (one or more hidden convolutional layers), and an output layer (Pesapane et al 2018).…”
Section: Common Ai Methods In Breast Imagingmentioning
confidence: 99%
“…As a subset of DL and the most common type of neural network, the CNN is suited to identify particular patterns in images which can occur at different locations because the convolution operation is spatially invariant (Burt et al 2018, Robertson et al 2018. In a systemic review, Nasser and Yusof found that CNN model has the most accurate performance with the most extensive application for breast cancer diagnosis (Nasser and Yusof 2023). A CNN consists of three layers: an input layer, a hidden layer (one or more hidden convolutional layers), and an output layer (Pesapane et al 2018).…”
Section: Common Ai Methods In Breast Imagingmentioning
confidence: 99%
“…CASE STUDY 2: BREAST CANCER DETECTION 1) Problems and goals. Early detection of breast cancer is important for increasing the chances of patients' survival [144]. A large part of clinical diagnosis in this area is concerned with characterizing various features of the tumor from mammograms, including masses, calcification, architectural distortion, asymmetries, and other related signs [145].…”
Section: A Case Study 1: Automated Initial Screening For Diabetic Ret...mentioning
confidence: 99%
“…Several studies have reviewed the application of deep learning in cancer research, highlighting its potential in advancing cancer diagnosis, prognosis, and treatment prediction. 57 , 58 …”
Section: Artificial Intelligence Application To Cancer Researchmentioning
confidence: 99%